Interferon regulatory factor-7 modulates experimental autoimmune encephalomyelitis in mice - Salem, Mohammad (BioMed Central, 2011)
BACKGROUND: Multiple sclerosis (MS) is an inflammatory disease of the central nervous system (CNS) with unknown etiology. Interferon-β (IFN-β), a member of the type I IFN family, is used as a therapeutic for MS and the IFN signaling pathway is implicated in MS susceptibility. Interferon regulatory factor 7 (IRF7) is critical for the induction and positive feedback regulation of type I IFN. To establish whether and how endogenous type I IFN signaling contributes to disease modulation and to better understand the underlying mechanism, we examined the role of IRF7 in the development of MS-like disease in mice. METHODS: The role of IRF7 in development of EAE was studied by immunizing IRF7-KO and C57BL/6 (WT) mice with myelin oligodendrocyte glycoprotein using a standard protocol for the induction of EAE. We measured leukocyte infiltration and localization in the CNS using flow cytometric analysis and immunohistochemical procedures. We determined levels of CD3 and selected chemokine and cytokine gene expression by quantitative real-time PCR. RESULTS: IRF7 gene expression increased in the CNS as disease progressed. IRF7 message was localized to microglia and infiltrating leukocytes. Furthermore, IRF7-deficient mice developed more severe disease. Flow cytometric analysis showed that the extent of leukocyte infiltration into the CNS was higher in IRF7-deficient mice with significantly higher number of infiltrating macrophages and T cells, and the distribution of infiltrates within the spinal cord was altered. Analysis of cytokine and chemokine gene expression by quantitative real-time PCR showed significantly greater increases in CCL2, CXCL10, IL-1β and IL17 gene expression in IRF7-deficient mice compared with WT mice. CONCLUSION: Together, our findings suggest that IRF7 signaling is critical for regulation of inflammatory responses in the CNS.